Russian influence, anti-Western sentiments and African agency: The struggle for influence in the Democratic Republic of Congo (The Strategic Review for Southern Africa, 2023)
Russia has been trying to extend its influence over Africa over the last years; a process which became intensified due to the Russia-Ukraine war. Through the case of the Democratic Republic of Congo (DRC), this article shows that although Russia plays an active role in this quest for influence by offering incentives (such as those shipments of weapons), anti-Western sentiments in the DRC are at least as important. These sentiments have been magnified by the M23 rebellion and perceptions of Western complicity in this crisis. This has resulted in pressure within the Congolese administration, particularly from the security forces, to “shift to Russia,” as well as Western efforts to counter this influence. At the same time, this ‘neo-Cold War’ has offered opportunities for political leverage by the Congolese government, to exercise pressure on Western governments – something which has not always been successful.
Keywords: Democratic Republic of Congo; Russia; Geopolitics; M23